THE INFLUENCE OF WEBSITE QUALITY, STORE PROMOTIONS, AND TIME PRESSURE ON E-IMPULSE BUYING ON SHOPEE - Harun Al Rasyid; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The study aims to examine the impact of website quality, store promotion, and time pressure on e-impulse buying on Shopee. The research uses primary data obtained by distributing questionnaires to 115 respondents selected through purposive sampling. The data analysis method employed is SEM-PLS, using Smart PLS version 4.0 as the analytical tool. To test data validity, the researcher uses validity tests including convergent validity, discriminant validity, and average variance extracted (AVE), as well as reliability tests such as model fit, coefficient of determination (R²), Q-square, and effect size. The results of this study indicate that website quality does not affect e-impulse buying on Shopee. The analysis found that students of Malikussaleh University do not consider website quality significantly. Store promotion has a significant effect on impulse buying on Shopee; Effective store promotions, such as discounts, special offers, and loyalty programs, tend to increase the urgency to make unplanned purchases. Time pressure also has a significant effect on impulse buying on Shopee. Time pressure, often manifesting as limited-time offers or flash sales, can increase the urgency to make immediate purchases without thorough consideration.